Effects of flame-retardant agents on mechanical properties and flammability of impregnated sugar palm fibre-reinforced polymer composites - Ibrahim, Abu Hatim (2013)
This research evaluated the effects of flame-retardant agents on mechanical properties and flammability of impregnated sugar palm fibre-reinforced polymer composites. The study was divided into three stages, where the first stage focused on the characterisation of tensile properties of sugar palm fibre (SPF) impregnated with thermosetting resins, such as unsaturated polyester, vinylester and epoxy resins were characterised. The results showed that the impregnation of thermosetting resins,which involved diffusing the resins into the lumen cells of sugar palm fibre (SPF),increased the stiffness. The tensile strengths of vinylester- (VE-)- impregnated, unsaturated polyester- (UP-)-impregnated and epoxy-impregnated fibres significantly increased to 158.31 MPa, 167.53 MPa and 188.06 MPa, respectively,compared with the tensile strength of the control specimen, 107.12 MPa. The maximum tensile modulus of SPF impregnated with epoxy, UP and VE were 21%,12.7% and 8.4% compared with non-impregnated SPF. The second stage of the study focussed on interfacial shear strength (IFSS) and the effects of embedded lengths of SPF reinforced with UP, VE and epoxy polymers by single fibre pull-out test (SFPT). The test samples were fabricated by inserting a fibre into a mixture of UP-impregnated fibre/UP, VE-impregnated fibre/VE and epoxyimpregnated fibre/epoxy. SFPT were conducted to examine the effect of embedded length on the IFSS of the fibre in the thermosetting matrix. The embedded length for the optimum IFSS of UP/UP was 4 mm at 2.67 MPa. The embedded length for the optimum IFSS for VE/VE was 5 mm at 2.46 MPa. The embedded length for the optimum IFSS of epoxy/epoxy was 3 mm at 3.25 MPa. The results showed that the IFSS gradually decreased as the embedded length increased. It was concluded that the embedded length for the optimum IFSS of the thermosetting matrix was 3 mm. The third stage of the study involved an investigation of the effect of impregnated SPF reinforced composites filled with aluminium trihydroxide (ATH) and magnesium hydroxide (MH) which served as flame retardant fillers. The SPF composites were impregnated with UP resin. The study investigated the effects of flame retardant fillers (FRF) with a loading range of 10% - 50%. The results showed that the tensile strength, tensile modulus and elongation at break of the composites filled with ATH were significantly higher than the tensile strength, tensile modulus and elongation at break of the composites filled with MH. The tensile strength decreased from 6.87 MPa to values ranging from 3.72 - 5.84 MPa and 3.16- 5.01 MPa for ATH- impregnated sugar palm fibre composites (ISPFC) and MH-ISPFC,respectively. The tensile modulus decreased from 1843.23 MPa to values ranging from 1179.62 - 1816.8 MPa and 1063.71 – 1522.99 MPa for ATH-ISPFC and MHISPFC,respectively. The elongation at break decreased from 8.17% to values ranging from 5.15 - 7.11 % and 3.61-7.41% for ATH-ISPFC and MH-ISPFC, respectively. The impact strength also decreased from 1.96 kJ/m2 to values ranging from 1.03 - 1.91 kJ/m2 and 0.97 - 1.54 kJ/m2 for ATH-ISPFC and MH-ISPFC,respectively. The fire propagation performance of core particle board of ISPFC filled with ATH and MH fillers were also investigated. The fire propagation test was evaluated using a performance index (I), which indicated the heat released from the tested particle boards. The result showed that, Both ATH-ISPFC and MH-ISPFC boards reduced the average performance index from 35.5 to values ranging from 22.0 - 25.6 and 21.5 – 31.5 for ATH-ISPFC and MH-ISPFC, respectively. In general, ATH-ISPFC exhibited better fire retardant performances for FRF loadings in range of 10wt%-40wt% FRF loadings but the fire performance for 50wt% FRF loading revealed that MH exhibits the optimal fire retardant performance. An increase in flame retardant fillers resulted in a negative effect on the mechanical properties of composite materials but yielded better fire retardant performances of the composites.